Congenital muscular dystrophy with severe retrocollis and mental retardation: a report of two siblings. Issue 3 (March 1997) - Nashef, L; Lake, B D; Schapira, A H
Abstract : Two siblings with a congenital muscular dystrophy and severe mental retardation which was not due to dystrophin, merosin, or adhalin deficiency are described. These cases overlap with congenital muscular dystrophy of the Fukuyama-type but are less severe. Atypical features include limited facial involvement, retained ambulation, and severe retrocollis.